2018
DOI: 10.24252/bio.v6i2.5010
|View full text |Cite
|
Sign up to set email alerts
|

Vegetasi Tumbuhan pada Kawasan Tepi Hutan Taman Nasional Gunung Gede Pangrango yang Berbatasan dengan Kebun Raya Cibodas

Abstract: Cibodas Botanic Garden area is adjacent with natural forest of Mt. Gede Pangrango National Park which consequences both vegetation in the border area are influence each other. The aims of this research were to study plant vegetation of forest area adjacent to Cibodas Botanical Garden and compare it with forest interior using transect method. The results showed that species richness in forest interior were higher than adjacent forest area. Furthermore, number of tree species, basal area and Shannon-Wienner dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
1
4
0
5
Order By: Relevance
“…Aglaia eximia and Polyalthia subcordates, showed a positive regeneration trend compared with a high trees (Table 4). Polyalthia subcordata, Sambucus javanica, and Aglaia eximia were commonly found on those heights, as reported by Zuhri et al (2018) in the remnant forest of Cibodas Botanic Gardens. Pinanga javana (Pinang jawa), is also spread throughout observation plots.…”
Section: Floristic Composition and Structure Vegetation Diversity Of supporting
confidence: 71%
See 2 more Smart Citations
“…Aglaia eximia and Polyalthia subcordates, showed a positive regeneration trend compared with a high trees (Table 4). Polyalthia subcordata, Sambucus javanica, and Aglaia eximia were commonly found on those heights, as reported by Zuhri et al (2018) in the remnant forest of Cibodas Botanic Gardens. Pinanga javana (Pinang jawa), is also spread throughout observation plots.…”
Section: Floristic Composition and Structure Vegetation Diversity Of supporting
confidence: 71%
“…The requirement of food and settlement has pressed to open much larger land (Setiawan and Sulistyawati 2008;van Welzen and Raes 2011;Tsujino et al 2016). On the other hand, diversity loss and dynamic vegetation succession that were often found in the mountain forest of Java (Zuhri and Mutaqien 2011;Purwaningsih et al 2017;Zuhri et al 2018), will encourage innovation to the conservation of the flora on every mountain, such as in Burangrang Nature Reserve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that sub-group IIA is a transition zone between utilization block and protected block, although more similar to protected block. The transition zone usually has the highest species number and unique composition of flora, as reported by Mutaqien and Zuhri (2011) and Zuhri et al (2018) in Mt. Gede Pangrango NP.…”
Section: Results and Discussion The Utilization Block Compared To Protection Block: A Species Compositionmentioning
confidence: 56%
“…Lokasi tersebut merupakan habitat bagi berbagai jenis burung (Partasasmita, Atsaury, & Husodo, 2017), primata jawa seperti Owa Jawa, Lutung dan Surili (Partasasmita & Malik, 2016), serta menjadi bagian penting dalam penyelamatan tumbuhan secara in situ hutan pegunungan di Jawa (Partasasmita & Malik, 2016;Susilo, 2018;Cahyanto, Efendi, & Ramdan, 2020). Seperti halnya, di kawasan hutan pegunungan lainnya di Jawa (Purwaningsih, Polosakan, Yusuf, & Kartawinata, 2017;Zuhri et al, 2018), hutan CA Gunung Tilu banyak didominasi dengan jenis tumbuhan Fagaceae dan Lauraceae, terutama jenis Castanopsis javanica (Cahyanto et al, 2020). Lokasi yang berbatasan langsung dengan perkebunan memunculkan komposisi flora yang unik, seperti yang ditemukan di Cagar Biosfer Cibodas (Zuhri et al, 2018).…”
Section: Pendahuluanunclassified